Factors associated with deaths by tuberculosis in the state of Mato Grosso, 2011-2020: retrospective cohort study - Vanessa da Silva Lopes; Rodrigo de Macedo Couto; Alexandre Peron da Luz; Pãmela Rodrigues de Souza Silva; Jaqueline Costa Lima (Ministério da Saúde do Brasil, 2024)
Abstract Objective: To investigate factors associated with tuberculosis deaths in Mato Grosso state, Brazil, from 2011 to 2020. Methods: Retrospective cohort study with data obtained from the Notifiable Health Conditions Information System and the Mortality Information System. Deaths were qualified using probabilistic linkage and analyzed using Poisson regression. Results: 12,331 cases and 525 deaths were identified over 10 years. The factors associated with death were: age ≥60 years (RR: 7.70; 95%CI 1.91;31.04), incomplete elementary and high school education (RR: 3.66; 95%CI 1.34;9.96), illiteracy (RR: 4.50; 95%CI 1.60;12.66), homeless population (RR: 2.41; 95%CI 1.34;4.35), alcohol use (RR: 1.45; 95%CI 1.04;2.02), male sex (RR: 1.48; 95%CI 1.04;2.09) and tobacco use (RR: 1.32; 95%CI 0.98;1.77). Laboratory confirmation was a protective factor. Conclusion: Risk of death was higher in men over 60 years old, with low education levels, in vulnerable situations, and who used alcohol/tobacco.